Advances in nano-based materials for glioblastoma multiforme diagnosis: A mini-review - Gusmão, Luiza Araújo; Matsuo, Flávia Sayuri; Barbosa, Hellen Franciane Gonçalves; Tedesco, Antonio Claudio (Frontiers in Nanotechnology, 2022)
The development of nano-based tools for diagnosis enables a more precise prognosis and results. Inorganic, organic, or hybrid nanoparticles using nanomaterials, such as quantum dots, extracellular vesicle systems, and polymeric nanoparticles, among others, with different molecular compositions, have been extensively explored as a better strategy to overcome the blood-brain barrier and target brain tissue and tumors. Glioblastoma multiforme (GBM) is the most common and aggressive primary tumor of the central nervous system, with a short, already established prognosis. The delay in early detection is considered a key challenge in designing a precise and efficient treatment with the most encouraging prognosis. Therefore, the present minireview focuses on new strategies presented recently in the literature regarding nanostructures' use, design, and application for GBM diagnosis.